2023
DOI: 10.1590/acb387523
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin in vasoplegic shock in surgical patients: systematic review and meta-analysis

Taís Felix Szeles,
Juliano Pinheiro de Almeida,
José Arnaldo Shiomi da Cruz
et al.

Abstract: Purpose: Vasoplegia, or vasoplegic shock, is a syndrome whose main characteristic is reducing blood pressure in the presence of a standard or high cardiac output. For the treatment, vasopressors are recommended, and the most used is norepinephrine. However, new drugs have been evaluated, and conflicting results exist in the literature. Methods: This is a systematic review of the literature with meta-analysis, written according to the recommendations of the PRISMA report. The SCOPUS, PubMed, and ScienceDirect d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…≤ 0.25 μg/kg/min (HR = 0.51; 95% CI: 0.27–0.94) [ 6 ]. This is a significant finding because a recently published meta-analysis including surgical patients did not document that the use of vasopressin (a widely used vasopressor) reduced the risk of death compared with the use of norepinephrine (OR = 1.60; 95% CI: 0.47–5.50) [ 7 ]. Also, another observational study found that the effect of AT was more beneficial when it was included at NED < 0.3 μg/kg/min [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…≤ 0.25 μg/kg/min (HR = 0.51; 95% CI: 0.27–0.94) [ 6 ]. This is a significant finding because a recently published meta-analysis including surgical patients did not document that the use of vasopressin (a widely used vasopressor) reduced the risk of death compared with the use of norepinephrine (OR = 1.60; 95% CI: 0.47–5.50) [ 7 ]. Also, another observational study found that the effect of AT was more beneficial when it was included at NED < 0.3 μg/kg/min [ 8 ].…”
Section: Introductionmentioning
confidence: 99%